2015
DOI: 10.1021/acs.iecr.5b02351
|View full text |Cite
|
Sign up to set email alerts
|

HCl Oxidation To Recycle Cl2 over a Cu/Ce Composite Oxide Catalyst. Part 2. Single-Tube-Reactor Simulation

Abstract: The pilot test is an important procedure that ultimately leads to implementation of an optimized catalytic process. A global reaction rate was calculated from the intrinsic kinetic rate with the effectiveness factor, and the calculated value is fitted well with the experimental data, which indicates that the global reaction rate is reliable. Further, a scale-up HCl oxidation experiment has been carried out in a single-tube reactor with an inner diameter of 22 mm using shaped CeO 2 −CuO/Y as the catalyst. A one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The kinetic model is applied in the simulated optimization of the tubular fixed-bed reactor. , The structure of the tubular fixed-bed reactor is shown in Figure , where catalyst is loaded in reaction pipes (φ32 × 2 in diameter, 3 m in length). The technology parameters are designed as follows: inside reaction pipes, reaction temperature T of 380 °C, reaction pressure P of 0.1 MPa, reactant molar ratio n HCl / n O 2 of 2, and HCl space velocity F HCl0 / W of 450 L (kg of catalyst) −1 h –1 ; outside reaction pipes, 40% NaNO 2 /60% KNO 3 molten salt used for heat transfer, molten salt flow rate F s of 16 m 3 /h, and molten salt temperature T s of 355 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic model is applied in the simulated optimization of the tubular fixed-bed reactor. , The structure of the tubular fixed-bed reactor is shown in Figure , where catalyst is loaded in reaction pipes (φ32 × 2 in diameter, 3 m in length). The technology parameters are designed as follows: inside reaction pipes, reaction temperature T of 380 °C, reaction pressure P of 0.1 MPa, reactant molar ratio n HCl / n O 2 of 2, and HCl space velocity F HCl0 / W of 450 L (kg of catalyst) −1 h –1 ; outside reaction pipes, 40% NaNO 2 /60% KNO 3 molten salt used for heat transfer, molten salt flow rate F s of 16 m 3 /h, and molten salt temperature T s of 355 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The active components and promoters are supported on the γ-Al 2 O 3 carrier with a diameter of 2 mm. In the prior test performed by Chlor-Alkali Chemical Co., Ltd., via simulation of the industrial reaction conditions, the long period performance of the catalyst activity has been evaluated on a single-tube reactor . The results show that the average HCl conversion is 75% and there is no obvious change in the long duration, which indicates the catalyst activity is stable.…”
Section: Methodsmentioning
confidence: 99%
“…Simulation of a single-tube reactor for HCl oxidation using CeO 2 –CuO/Y catalyst was reported earlier by Chen et al The material, energy,and momentum balance equations have been reported as follows (eqs –): …”
Section: Reactor Modelmentioning
confidence: 99%